Pelvic digit: What are you pointing at? - Lik Han, Ong; Yoke Foong, Amy Wong; Faris Indra Prahasta, Didi Indra; Mohamad Zaki, Mohd Amin (ELSEVIER, 2022)
A pelvic digit is a rare congenital anomaly and is often discovered incidentally. We present a 44-year-old male patient with bilateral pelvic digits discovered on a pelvic radiograph during a primary survey after a road traffic accident. Supplementary imaging using computed tomographic imaging confirmed the bilateral finding which is rare. No surgical attempt was made at removal as the patient remained asymptomatic.